2016
DOI: 10.1111/cts.12422
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Maximum Recommended Therapeutic Dose Using Predicted Promiscuity and Potency

Abstract: We report a simple model that predicts the maximum recommended therapeutic dose (MRTD) of small molecule drugs based on an assessment of likely protein–drug interactions. Previously, we reported methods for computational estimation of drug promiscuity and potency. We used these concepts to build a linear model derived from 238 small molecular drugs to predict MRTD. We applied this model successfully to predict MRTDs for 16 nonsteroidal antiinflammatory drugs (NSAIDs) and 14 antiretroviral drugs. Of note, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was also reported that low MRTD drugs often have high pseudo-potency (Liu et al, 2016). On the other hand, drugs of low pseudo-potency need high dose to reach the desired therapeutic effects (Liu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that low MRTD drugs often have high pseudo-potency (Liu et al, 2016). On the other hand, drugs of low pseudo-potency need high dose to reach the desired therapeutic effects (Liu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These predicted MRTD dose can be instrumental to estimate the starting dose in phase I clinical trials, reducing the number of animals used in preliminary toxicology studies (Schymanet al, 2017). It was also reported that low MRTD drugs often have high pseudo-potency (Liu et al, 2016). On the other hand, drugs of low pseudo-potency need high dose to reach the desired therapeutic effects (Liu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…(Ferreira & Andricopulo, 2019) Category 0 indicates FDAMDD negative while category 1 indicates FDAMDD positive nature. (Liu, Oprea, Ursu, Hasselgren, & Altman, 2016) The highest FDAMDD value was found for nos88 while the lowest value is found for nos37.…”
Section: Toxicity Properties Of Top-six Noscapinesmentioning
confidence: 87%
“…The Drug-binding Dataset collects 984 high-quality 3D structures (x-ray resolution higher than 2.5 Å) that co-crystalized with FDA approved small molecule drugs (non-nutraceuticals), representing binding environments of 284 distinct drugs [50]. The Human Off-target Dataset comprises 2271 proteins representing a non-redundant representative set (90% percent identity) of human proteins and their close homologs that have high quality 3D structures (x-ray resolution higher than 2.5 Å) in PDB[51]. We have applied PocketFEATURE[46] to predict the probability of binding between the 284 drugs and the 2271 potential off-targets.…”
Section: Methodsmentioning
confidence: 99%